Administrative Transparency in Public Secondary Schools in Jordan - Serhan, Khaled (European Scientific Journal, ESJ, 2016)
This study aimed to probe the degree to which public secondary school principals exercise administrative transparency in Jordan, as well as study the effect gender, educational background and years of experience have on the degree of exercising it. The study population consisted of all public secondary school principals working at the Directorate of Education in First Zarqa area for the academic year 2015-2016. The study sample consisted of (263) teachers who were selected randomly. A questionnaire was developed consisting of (22) items using appropriate statistical methods to obtain the results. The study results showed that the degree of exercising administrative transparency was moderate in the fields of Information Clarity and Administrative Accountability, while it was low in the Participation field. In light of the results, the study presented a set of recommendations, such as raising awareness among school principals of the importance of exercising administrative transparency across all of its domains.